Kesadaran Pajak, Transparansi dan Kualitas Layanan: Dampak Kepatuhan Dimoderasi oleh Penggunaan Surat Keterangan Pemotongan Pajak Secara Elektronik - Joni Joni; Estralita Trisnawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study investigates the influence of tax awareness, transparency and service quality on taxpayer compliance, specifically examining the moderating role of e-Bupot. The research was conducted at KPP Pratama Batam Selatan, utilizing a quantitative approach with a sample of 100 taxpayers. Primary data were collected via questionnaires and analyzed using the PLS-SEM method with SmartPLS 3.0. The empirical confirm that Tax Awareness and Transparency show a positive significant influence on Taxpayer Compliance across both regression models. Service Quality only achieved a significant positive effect in the more comprehensive moderated model, indicating the importance of administrative support. The E-Bupot digital platform proved to be a selective yet critical moderator. It significantly strengthened the positive effects of both Tax Transparency and Service Quality, acting as a powerful catalyst for systemic and procedural efficiency. Conversely, E-Bupot's interaction with Tax Awareness was not significant. This outcome implies that high internal awareness is insufficient for maximizing digital compliance efforts without corresponding digital literacy and technological readiness among taxpayers.